Price, Promotion, and Supporting Facilities on Customer Satisfaction - Gunawan Bata Ilyas; Heriyanti Mustafa (Manunggal Halim Jaya, 2022)
Business development today has been colored by various competitions in all fields. Seeing these conditions makes business people increasingly required to have the right strategy in meeting sales volume targets. Moreover, given the increasingly dynamic development of technology, humans are required quickly and appropriately to act to not be less competitive This research is qualitative research using a questionnaire to collect the data. Data analysis was performed using the multiple linear regression method. This study aimed to determine price, promotion, and supporting facilities on customer satisfaction at Hotel Atria Inn Makassar. In this study, the regression test was used to test hypotheses. Theoretically, there is an influence between independent variables consisting of prices, promotions, and supporting facilities against dependent variables customer satisfaction. Based on the study results, the conclusions in this study are as follows: (1) Prices have a positive and significant effect on customer satisfaction at Hotel Atria Inn Makassar. (2) Promotions have a positive and significant effect on customer satisfaction at Hotel Atria Inn Makassar. (3) Facilities have a positive and significant effect on customer satisfaction at Hotel Atria Inn Makassar. (4) Prices, promotions, and Facilities positively affect partially and simultaneously Customer Satisfaction at Hotel Atria Inn Makassar.